Desenvolvimento de ferramenta mobile para gerenciamento e comércio de resíduos da construção civil com proposição de metodologia de precificação - Teixeira, Paulo Júnio Rodrigues (2021)
The generation of waste in civil construction (CW) will never be zero and the search for other solutions before the simple disposal, should be a continuous improvement aimed by the management and environmental responsibility sectors of the companies in the sector. Both demolitions and new construction sites present residues that are not at the end of their useful life cycle and can be reused in the construction site itself or in other constructions. The circular economy aims to bring the waste to the beginning of the production chain, giving it value as a material, allowing its reuse, reducing costs and preserving the sources of resources. The integrated system of the waste exchange, on the other hand, aims to reduce the emission of debris through the integration of various sectors of the industry, by ensuring and allowing the marketing of by-products from one sector, with a focus on reuse in others. In this context, the present work aimed to develop and present a mobile tool, which enables the value of waste as a product on a trading platform, and allows the presentation of recycling techniques, through a database of scientific papers. For this, a systemic review methodology was proposed, to identify recent studies on methods of reuse and recycling of CWs, which later came to integrate the software. It was also suggested to determine the costs of the materials lost in a stationary waste bucket, to verify the tool's compliance to the concepts of the waste bag. Finally, 14 papers presenting recycling techniques were reached and the result of R$1080.53 was obtained, when pricing the waste in the bucket. From these and other data, a mobile application was developed that, in addition to assisting in the management and disposal, lists possibilities of reintegration and commercialization of CWs.